(untitled) (The Agriculturists, 2013)
A preliminary investigation was carried out under the AEZ- 29 at the Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Pahartali, Chittagong during December 2010 to May 2012 to evaluate two dragon fruit genotypes. The longer plant (272.13 cm) was recorded in HUP 002 while it was 263.34 cm in HUP 001 after one and half year of planting. Flower bud emergence took place after 17 months (on 9 May, 2012) in HUP 001, while it commenced in HUP 002 after 15 months (on 22 March, 2012). Flower bud required 28 days bloom from emergence and the fruit matured after 33 days from anthesis in HUP 001, while that required 35 days for HUP 002 and fruits become matured after 32 days from anthesis. Larger number (8) of flowers per plant was observed in HUP 002 while the lower was noted in HUP 001(6). Numerous anthers were observed below the stigma with attractive white petals in both the varieties. The fruit weights ranged from 200 -375 in HUP 002 but 150-200g in HUP 001. The edible portions were 91.0 and 92.0 with 12.0 and 11.4 % TSS in HUP 001 and HUP 002, respectively. Fruit pulp colour was white in HUP 001 while red in HUP 002. DOI: http://dx.doi.org/10.3329/agric.v11i2.17487 The Agriculturists 2013; 11(2) 52-57